Optimalisasi Ekonomi Kreatif Dengan Memanfaatkan Belimbing Wuluh Sebagai Penguatan Program Wirausaha MBKM Pada Kelurahan Rabangodu Selatan Kota Bima - Kartin Aprianti; Puji Muniarty; Mawar Hidayati; Muhammad Yusuf; Nurlita Apriyanti; Sahrun Hasan (CV. Devi Tara Innovations, 2024)
Freedom to Learn Independent Campus (MBKM) Entrepreneurship activities are students' freedom to study outside of higher education. Through collaboration with various universities, students will be involved in entrepreneurial learning which builds entrepreneurial spirit, gains entrepreneurial experience, and improves students' work abilities. The aim of community service activities carried out by KKNT_MBKM STIE BIMA students is to empower the local community by utilizing the local potential of the starfruit plant more optimally. This empowerment is carried out through product innovation in the form of sweets, juice drinks and masks as well as attractive product packaging. The methods used in this service activity are socialization, training and mentoring through the preparation, implementation and monitoring and evaluation stages of activities. This community service activity produces various processed products from the starfruit plant which are packaged firmly and safely with attractive designs.